Evaluation of a Dutch school-based depression prevention program for youths in highrisk neighborhoods: study protocol of a two-armed randomized controlled trial - Kindt Karlijn CM; van Zundert Rinka; Engels Rutger CME (BMC, 2012)
Abstract Background Research has indicated that depression prevention programs attenuate the development of symptoms of depression in adolescents. To implement these programs on a large scale, implementation in a school setting with teachers providing the programs is needed. In the present study, the effectiveness of the Dutch depression prevention program Op Volle Kracht (OVK) provided by school teachers during school hours with adolescents from high risk neighborhoods will be tested. The mediating effects of cognitive distortions and alexithymia will be evaluated as well. We hypothesize that the OVK program will prevent or decrease reported depressive symptoms, and that this association will be mediated by cognitive distortions and alexithymia. Methods/Design Schools with at least 30% of their pupils living in low income areas in the Netherlands are invited to participate in the study. Classes from vocational training up to pre-university level are eligible and 1324 adolescents (11-14 years) will be participating in the study. Randomisation will be done at class level, randomly assigning participants to an intervention group (OVK) and a control group (care as usual), stratifying by school level (high versus low). Trained school teachers will be delivering the program, which covers cognitive-behavioral and social problem-solving skills. Longitudinal data will be collected with self-report measurements administered in the school setting at baseline, post intervention and at two follow ups (at 6 and 12 months). Primary outcome is the level of depressive symptoms, and secondary outcomes include: cognitive errors, response style, attributional style, alexithymia, stressful life events, substance use, happiness, and school grades. Discussion If the OVK program proves to be effective when it is provided by school teachers, a structural implementation of the program in the school curriculum will enhance the quality of the lives of adolescents and their families and will reduce costs in health care. In addition, the results of the study advances current knowledge on the underlying mechanisms of the development of depression and may aid the improvement of depression prevention programs in general. Trial registration Dutch Trial Register NTR3110